Adaptation of Islamic Finance to the Performance of MSMEs in the Halal Food Industry - Muji Gunarto; Pitri Yanti (ETIKONOMI, 2024)
Research Originality: The findings of this research will contribute to the Islamic finance literature by answering the research gap between the relationship between MSME adaptation of Islamic finance implementation and MSME performance and providing practitionerinsight for policymakers and MSMEs in the halal food industry.Research Objectives: This study aims to determine the adaptation of Islamic finance to the performance of MSMEs in the halal food industry. Research Methods: The method used a quantitative and explanatory approach. The number of samples in this study was 212 MSME units taken by simple random sampling (SRS). The number of samples in this study is based on the needs of the analytical tools used. The analysis technique used is the structural equation model (SEM) approach with the help of the LISREL program.Empirical Results: The main findings show that halal industry MSMEs that adapt to Sharia finance tend to have a higher level of innovation than those that do not. Data shows that financing by Sharia principles enables MSMEs to allocate their resources more effectively, strengthening their ability to innovate in products and services. Innovations carried out by halal industry MSMEs that adopt a Sharia financial approach are more consistent with Sharia values, which leads to increased acceptance by Muslim consumers.Implications: MSME halal industry managers may consider adopting Islamic finance strategies as part of their business plans. This adoption includes using Sharia financing, investing according to Sharia principles, and managing their finances according to Sharia values. Managers also need to actively develop networks and collaborate with other stakeholders, including Sharia financial institutions, educational institutions, and other companies in the halal industry ecosystem.JEL Classification: D14, G21, L25How to Cite:Gunarto, M., & Yanti, P. (2024). Adaptation of Islamic Finance to the Performance of MSMEs in the Halal Food Industry. Etikonomi, 23(2), 369 – xx. https://doi.org/10.15408/etk.v23i2.34271.